TRIASTHLET (Three Eyes of Athlete Welfare): Upaya Perlindungan Hukum dan Hak Atas Kesejahteraan Atlet Sepak Bola pada Masa Pandemi Covid-19 di Indonesia - Herlin Sri Wahyuni; Irqi Sheva Maulana; Luna Dezeana Ticoalu (CV Rewang Rencang, 2021)
Soccer athletes currently have a condition that is exacerbated by the Covid-19 pandemic. One of them is related to the current work contract of soccer athletes and also how to resolve disputes related to the problem. Therefore, the authors make an alternative solution to the problem, namely